An experimental setup of multi-intelligent control system (MICS) of water management using the Internet of Things (IoT). (January 2020) - Hadipour, Morteza; Derakhshandeh, Javad Farrokhi; Shiran, Mohsen Aghazadeh
Abstract: In the 21th century water management using new technologies is a must due to the rapid growth of population, drought, and water scarcity. The Internet of Things (IoT) system with wireless devices can be employed to achieve this requirement. This paper introduces an innovative technique of multi-intelligent control system (MICS) of a water pump and a pump station, which is practically designed, set up, and used in an agricultural sector. The main component of MICS consists of three control systems, including the electro-pump controller, water level in reservoir and alarm control system. The entire system is governed by the IoT technology and operated via SMS or ringtone, which is manageable from anywhere at any time. A soft starter mechanism was designed and considered for running the electro-pump to eliminate the electrical shocks and mechanical stresses. In the proposed control system, a 4-state switch was designed and employed, which facilitates running and operating the system manually, automatically, using IoT state, and finally in off mode state. Description of the control and power circuits of the system are explained in detail. MICS is a very reliable system and provides a convenient and satisfactory solution for water management in the agricultural and industrial sectors as well as domestic consumption. The model is applied to a practical case study to demonstrate the effectiveness of the proposed control system. It is found that in addition to increasing the efficiency and productivity of the water management system, up to 60% of water can be saved by employing MICS via IoT. Highlights: An innovative technique of multi-intelligent control system (MICS) of a water pump and a pump station is designed and employed. The entire system can be governed by the Internet of Things (IoT) technology and operated via SMS or Ringtone. MICS has a very reliable operation and provides a convenient solution for water management with high accuracy. This intelligent system can be widely employed in different applications such as the agricultural and industrial sectors due to the robust and flexible construction. Huge amount of cost and water can be saved using MICS.